An Apple for teacher (education)? Reconstituting teacher professional learning and expertise via the Apple Teacher digital platform. (2022) - Lewis, Steven
Highlights: Apple Teacher users are both producers and consumers of content, or prosumers . Apple leveraging the need for remote learning during COVID school disruptions. Apple Teacher repositions Apple as a global education authority and expert. Abstract: Although COVID-19 has intensified clear global trends towards the digitalisation of schooling and the increasing role of information technology in education, a less obvious consequence has been the shift to online professional learning for teachers themselves. Informed by an emerging critical literature of digital education platforms, this paper will explore how Apple Teacher – the digital learning platform of the US technology giant, Apple Inc. – forges new marketised and platformed relations between schooling spaces and actors. I argue that Apple Teacher helps Apple to maximise its policy relevance, allowing it to leverage its global brand recognition to compellingly promote a particular vision of teacher knowledge and expertise.